Managing Personalization and Collaboration in Education: A Systematic Review of Educational Practices - Hasanah, Enung (JURNAL AL-TANZIM, 2024)
This systematic literature review analyzes 20 carefully selected documents from the Scopus database. This study explores ways that align with Islamic educational management's principles to balance personalized learning outcomes and community empowerment in academic settings. The selection of documents is based on relevance to the focus and recent developments in Islamic education. The qualitative analysis method uses thematic coding and VOS Viewer. The analysis results indicate that Islamic approaches like collaboration, reflection, and feedback can achieve balanced learning outcomes. Collaborative filtering helps select learning materials according to student's needs, while reflection and feedback strengthen positive interactions and ukhuwah within the learning community. In addition, computer-based learning and e-learning allow students to learn at their own pace. A flexible curriculum allows for adjustments to students' interests by the principle of taysir (making it easy). These findings recommend that educational institutions integrate a multifaceted approach to create an inclusive, adaptive, and Islamic-oriented learning environment.